1994
DOI: 10.3109/02841869409098447
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors in Chemoprevention of Cancer: An overview

Abstract: In the search for chemopreventive agents for cancer many natural products have been identified. Among them extensive experimental studies have been made on protease inhibitors which not only occur naturally in many plant products, but have also been synthesized in the laboratory. Many of these studies reveal the fact that protease inhibitors are able to prevent carcinogenesis and tumour promotion. A review of the reports available to date suggests that protease inhibitors are potential chemopreventive agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Yet many trypsin inhibitors did not exhibit significant anti-proliferative effects, such as the trypsin inhibitors from black gram seeds 29 , green lentil seeds 30 and lily bulbs 31 . Some reports have suggested that the anti-proliferative activity from animal protease inhibitors is based on their anti-protease activity 32,33 . However, whether the same is also true of plant trypsin inhibitors is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Yet many trypsin inhibitors did not exhibit significant anti-proliferative effects, such as the trypsin inhibitors from black gram seeds 29 , green lentil seeds 30 and lily bulbs 31 . Some reports have suggested that the anti-proliferative activity from animal protease inhibitors is based on their anti-protease activity 32,33 . However, whether the same is also true of plant trypsin inhibitors is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Other biotechnological application reported for protease inhibitors is that they can inhibit growth of transformed cells, i.e. thereby showing anticarcinogenic properties (Clawson, 1996;Das and Mukhopadhyay, 1994;Kennedy, 1998).…”
Section: Introductionmentioning
confidence: 98%